Factors Associated With Tb Treatment Outcomes in Patients with TB in Ridge Hospital - Mawuta, K.H. (University of Ghana, 2017)
Introduction: The convergence of TB and HIV dual epidemics are major public health challenges in Ghana as well as many developing countries. Globally, the TB epidemic is fuelled by the HIV epidemic. The chances of death in TB-HIV co-infected patients are higher than TB only patients as reported by most studies. Treatment outcome monitoring is a vital part of the surveillance needed to successfully eliminate TB. Aim: The study was conducted to determine the factors associated with TB treatment outcomes in patients with TB-HIV co-infection and TB only infection in the Ridge Hospital. Method: This was a retrospective cross sectional study carried out at the Ridge Hospital. It involved review of TB treatment cards of patients who received treatment for tuberculosis in the DOT center of the hospital from 2008-2016. Data on age, sex, distance from place of residence to DOTS center, type of patient, treatment supporter, diabetes, diagnostic category, duration of treatment, adverse drug reactions and treatment outcome were extracted on TB only infected and TB/HIV co-infected patients. Chi square test, binary and multiple logistic regression models were used to assess factors associated with adverse treatment during treatment. Results: Out of the 758 patients with complete records that were analyzed in this study, 45.6% (346/758) were cured, 42.5% (322/758) completed treatment. About 11.8% (90/758) of the patients had an adverse outcome which comprises of treatment outcomes; treatment failure, defaulting and death. Overall treatment success for all TB patients was 88.2% (668/758). TB-HIV co-infected patients treatment success was 77.6% (136/668). TB only patients’ treatment success was 91.3% (532/668). The prevalence of HIV among the TB cases was 23.2% (176/758). Independent predictors of adverse treatment were found to be; being HIV positive (AOR: 3.85, 95% CI: 2.19-6.75; p <0.01); aged 65 and above (AOR-1.76, 95% CI 1.44-1.54; p-0.01); previously failed TB treatment (AOR: 5.02, 95% CI 2.09-28.87; p <0.01). Conclusion: The 23.2% prevalence rate of HIV among TB cases confirms a report issued by the Ghana Aids Commission in 2009. The overall treatment success in this study is higher than Ghana’s success rate for 2011 of 86.5% and 84% success rate for new and relapse TB cases in Ghana in 2012. Patients who are advanced in age (>65 years), patients co-infected TB-HIV, and patients who have previously failed treatment, patients who reacted to anti-TB drugs were more likely to experience adverse treatment outcomes.
Thesis (MPH)
Keywords: Factors; Ridge Hospital; Patients with TB; Associated; TB Treatment Outcomes